philosophy of Educational body according to the change of century - رحيم عزيز, حسين; دحام منصور, فاضل; كريم هظل, عامر (Journal of College of Education, 2019)
The aim of the research is to know• The level of the philosophy vision to the physical Education for the student of the University .2.To the sing of differences  to the level of the philosophy vision for to the student of the University .• The resent research depends on the equal randomness sample . the sample Consists of 100 one hundred /male student /female students .by 50 male and 50 female.• The researchers build two evalnation criteria to the philosophy for physical education to students of the university and the criteria of the changes of era in the phylosophy of physical education to the students.• and the resent research has got the following results.1.The students have their own phylosophy for the physical education.2.The sign of difference in the level of the phylosophy of physical education to the male students.3.The medium accountancy refers to the sample of the recent research higher than the medium assumption to the physical education .And the recent research recommended the following:• To renew the educational mind by helding sessions to the professors and the students.• To join the advanced technology with the culture of the one who is going to raise this culture for the physical education.• To modernize a good program of training in the phylosophy of physical education by using computers and the means of the social communicationAnd the recent research give many suggestions :• Make study for electronic IT programme and its relationship with the phylosophy comprehension for the students of university .• make study of renew in the educational thinking and its relationship with the educational curriculum to the students of the university .